CRISPR/Cas9‐Mediated Fluorescent Tagging of Endogenous Proteins in Human Pluripotent Stem Cells. (24th January 2018) - Sharma, Arun; Toepfer, Christopher N.; Ward, Tarsha; Wasson, Lauren; Agarwal, Radhika; Conner, David A.; Hu, Johnny H.; Seidman, Christine E.
Abstract: Human induced pluripotent stem cells (hiPSCs) can be used to mass produce surrogates of human tissues, enabling new advances in drug screening, disease modeling, and cell therapy. Recent developments in clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 genome editing technology use homology‐directed repair (HDR) to efficiently generate custom hiPSC lines harboring a variety of genomic insertions and deletions. Thus, hiPSCs that encode an endogenous protein fused to a fluorescent reporter protein can be rapidly created by employing CRISPR/Cas9 genome editing, enhancing HDR efficiency and optimizing homology arm length. These fluorescently tagged hiPSCs can be used to visualize protein function and dynamics in real time as cells proliferate and differentiate. Given that nearly any intracellular protein can be fluorescently tagged, this system serves as a powerful tool to facilitate new discoveries across many biological disciplines. In this unit, we present protocols for the design, generation, and monoclonal expansion of genetically customized hiPSCs encoding fluorescently tagged endogenous proteins. © 2018 by John Wiley & Sons, Inc.